Access to diabetes diagnosis in Brazil based on recent testing and consultation: The Brazilian national health survey, 2013 and 2019 - Santos, Karine Brito Matos; Reis, Rodrigo Citton P. dos; Duncan, Bruce B.; D’Avila, Otávio Pereira; Schmidt, Maria Inês (Frontiers in Endocrinology, 2023)
Background: Screening for undiagnosed diabetes using glucose testing is recommended globally to allow preventive action among those detected. Our aim was to evaluate the access to glucose testing to screen for diabetes in Brazil using self-reported information on recent testing and medical consultation from national surveys of Brazilian adults. Methods: The Pesquisa Nacional de Saúde (PNS) was conducted in 2013 and 2019 drawing probabilistic samples of Brazilians aged 18 years and above. To evaluate glucose testing among those undiagnosed, we excluded those self-reporting a previous diagnosis of diabetes. We then defined recent access to diabetes diagnosis by considering the previous two years and choosing the last blood glucose test and the proximal medical consultation reported. We used Poisson regression with robust variance to assess correlates of access, expressing them with adjusted prevalence ratios (PR) and their 95% confidence intervals. Results: Access to recent glucose testing documented that over 70% reported a recent glycemic test, 71% in 2013, and 77% in 2019. These findings are consistent with a wide recent access to medical consultation, 86% and 89% in 2013 and 2019, respectively. Reporting recent glucose testing and medical consultation may better reflect the actual access to medical diagnostic testing. When analyzing this joint outcome, diagnostic access was still wide, 67% and 74%, respectively. Greater access (p< 0.001) was seen for women (PR=1.16; 1.15-1.17), older individuals (PR=1.25; 1.22-1.28), and those with higher education (PR=1.17; 1.15-1.18), obesity (PR=1.06; 1.05-1.08), and hypertension (PR=1.12; 1.11-1.13). In contrast, lower access (p<0.001) was seen for those declaring being Black (PR=0.97; 0.95-0.99) or of mixed-race (PR=0.97; 0.96-0.98), those residing in rural areas (PR=0.89; 0.87-0.90), and not having a private health insurance plan (PR=0.85; 0.84-0.86). Conclusions: Although access to diagnostic testing for diabetes is high in Brazil, partly due to its universal health system, social inequities are still present, demanding specific actions, particularly in rural areas and among those self-declaring as being Black or mixed-race.